Pengaruh Pemberian Aromaterapi Lemon Terhadap Penurunan Intensitas Nyeri Disminorea Pada Remaja - Zahrotun Naqiyah Sabrina Putri; Neny Yuli Susanti; Eliyawati (WOMB Midwifery Journal, 2025)
Dysmenorrhea is one of the disorders often experienced by adolescent girls during menstruation, which is characterized by pain in the lower abdomen. Non-pharmacological treatment of dysmenorrhea, one of which is by using lemon aromatherapy containing limonene compounds that can inhibit the work of prostaglandins and provide a relaxing effect. This study aims to determine the effect of lemon aromatherapy on the intensity of dysmenorrhea pain in adolescent at the Nurul Qoni’ Dormitory, Salafiyah Syafi’iyah Sukorejo Situbondo Islamic Boarding School. The method used is a quasi-experiment with a two-group pretest-posttest design. The sample consisted of 60 people, divided into intervention and control groups, each consisting of 30 people. Pain measurement was carried out using the Visual Analogue Scale (VAS). The results showed that the average pain scale before the intervention in the intervention group was 3.67 and after the intervention decreased to 0.53. in the control group, the average pain only changed slightly from 4.10 to 2.87. the Wilcoxon Signed Rank Test statistical test showed p value = 0.000 (p<0.05), which means that there is a significant effect of lemon aromatherapy on reducing the intensity of dysmenorrhea pain. The conclusion of this study is that lemon aromatherapy is effective in reducing dysmenorrhea pain and can be used as an alternative non-pharmacological therapy for adolescent girls.